Spatial variation of flow characteristics in a subarctic meandering river in ice-covered and open-channel conditions : A 2D hydrodynamic modelling approach - Lotsari, Eliisa; Tarsa, Tiia; Kämäri, Maria; Alho, Petteri; Kasvi, Elina (Earth Surface Processes and Landforms, 2022)
To be able to understand year-round river channel evolution both at present and in the future, the spatial variation of the flow characteristics and their sediment transport capabilities under ice cover need to be detected. As the measurements done through cross-sectional drill holes cover only a small portion of the river channel area, the numerical simulations give insight into the wider spatial horizontal variation of the flow characteristics. Therefore, we simulate the ice-covered flow with a hydrodynamic two-dimensional (2D) model in a meandering subarctic river (Pulmanki River, Finland) in mid-winter conditions and compare them to the pre-winter open-channel low flow situation. Based on the simulations, which are calibrated with reference measurements, we aim to detect (1) how ice-covered mid-winter flow characteristics vary spatially and (2) the erosion and sedimentation potential of the ice-covered flow compared to open-channel conditions. The 2D hydrodynamic model replicated the observed flow characteristics in both open-channel and ice-covered conditions. During both seasons, the greatest erosional forces locate in the shallow sections. The narrow, freely flowing channel area found in mid-winter cause the main differences in the spatial flow variation between seasons. Despite the causes of the horizontal recirculating flow structures being similar in both seasons, the structures formed in different locations depended on whether the river was open or ice covered. The critical thresholds for particle entrainment are exceeded more often in open-channel conditions than during ice-covered flow. The results indicate spatially extensive sediment transport in open-channel conditions, but that the spatial variability and differences in depositional and erosional locations increase in ice-covered conditions. Asymmetrical bends and straight reaches erode throughout the year, whereas symmetrical, smaller bends mainly erode in open-channel conditions and are prone to deposition in winter. The long ice-covered ...